Elasticidades dinâmicas do investimento no crescimento econômico do Ceará: uma análise do período 2003-2019 - Nascimento, André Luiz Sales (2024)
This dissertation explores the role of public and private investments in the growth process of Ceará, Brazil. Specifically, we assess the dynamic elasticities of these investments for the period spanning from the first quarter of 2003 to the fourth quarter of 2009. The dynamic estimates were conducted based on the Flexible Least Squares (FLS) methodology proposed by Kalaba and Tesfatsion (1989). Our findings suggest that the elasticity of private investment exceeds that of public investment for the entire analyzed period, regardless of the smoothing criterion of the estimator employed (Matrix or Kalman filter). Furthermore, the dynamic behavior of these elasticities exhibits a growing trend and is consistent throughout the examined period. This implies that these investments tend to be complementary to the economy of Ceará, and this degree of complementarity has been evolving over the analyzed timeframe. Public policies should offer fiscal and financial incentives to stimulate private investments in infrastructure, innovation, technology, and workforce training. The idea is that these incentives will make investments more attractive to companies, resulting in broad economic benefits for the state.